Novel Design for a Diffusive Solar Cell Window. (5th July 2015) - Chen, Ruei-Tang; Kang, Chih-Chieh; Lin, Jeng-Feng; Chiou, Sheng-Wei; Cheng, Hung-Hsiang; Lai, Chih-Wen
Abstract : Building integrated photovoltaics (BIPV) are an important application of future solar energy development. The incorporation of solar cells into windows must not only maintain indoor natural lighting but also generate electrical power at the same time. In our continuing effort to improve the design of diffusion solar window, a more fundamental and efficient three-layer structure—glass/EVA with TiO2 nanoparticles embedded/glass—was proposed. In this work, a well-established ASAP ray-tracing model for a diffusive solar cell window was implemented to validate the outperformance of three-layer structure over primitive five-layer structure. Optical simulations were also implemented to perform its primary design for the determination of the optimal design parameters, such as the glass thickness, the EVA thickness, and the weight concentration of TiO2 nanoparticles. Based on the simulation results, an optimal design for a three-layer diffusive solar cell window prototype was proposed. And the influence of both EVA thickness and glass thickness on the power edge-exitance (solar cell power generation efficiency) of a DSCW was thoroughly investigated.